Discovery of thiazostatin D/E using UPLC-HR-MS2-based metabolomics and σ-factor engineering of Actinoplanes sp. SE50/110 - Schlüter, Laura; Hansen, Kine Østnes; Isaksson, Johan; Andersen, Jeanette Hammer; Hansen, Espen Holst; Kalinowski, Jörn; Schneider, Yannik Karl-Heinz (Frontiers in Bioengineering and Biotechnology, 2024)
As the natural producer of acarbose, Actinoplanes sp. SE50/110 has high industrial relevance. Like most Actinobacteria, the strain carries several more putative biosynthetic gene clusters (BGCs) to produce further natural products, which are to be discovered. Applying a metabolomics-guided approach, we tentatively identified five further compounds that are produced by the strain: watasemycin, thiazostatin, isopyochelin, pulicatin, and aerugine. A comparison of the genomic context allowed the identification of the putative BGC, which is highly similar to the watasemycin biosynthetic gene cluster of Streptomyces venezuelae. In addition to the identified molecules, a thiazostatin-like compound was found. Isolation and structure elucidation with 1D and 2D NMR and HRMS were applied. The fraction containing m/z 369.0929 [M + H]+ comprised two highly similar compounds identified as thiazostatin D and thiazostatin E. The compounds possessed the same phenol–thiazole–thiazole molecular scaffold as the previously reported thiazostatin and watasemycin and have anti-proliferative activity against the breast adenocarcinoma cell line MCF7 and human melanoma cell line A2058, while no activity again the non-malignant immortalized fibroblast cell line MRC-5 was observed. We further showed that the manipulation of global transcriptional regulators, with sigH (ACSP50_0507) and anti-anti-σ factor coding ACSP50_0284 as an example, enabled the production manipulation of the 2-hydroxyphenylthiazoline family molecules. While the manipulation of sigH enabled the shift in the peak intensities between the five products of this pathway, ACSP50_0284 manipulation prevented their production. The production of a highly polar compound with m/z 462.1643 [M + H]+ and calculated elemental composition C19H27NO12 was activated under the ACSP50_0284 expression and is exclusively produced by the engineered strain.